Management of the early postoperative PCR positive patients in the COVID-19 pandemic: cardiac surgeon's nightmare - As, Ahmet Kağan; Yavuz, Senol (The European Research Journal, 2022)
Objectives: In the last 2 years with the new type of coronavirus infection (COVID-19) pandemic, it has become inevitable to adapt to this disease in cardiovascular surgery procedures. In this study, we aimed to investigate the effects of the results of respiratory tract samples taken from different places in patients undergoing cardiac surgery on our postoperative patient follow-up procedures and to share our cardiac surgery experiences during the pandemic period. Methods: A total of 177 patients who underwent cardiac surgery were included in this study. Endobronchial lavage samples were obtained from the intubated patients through the endotracheal tube in the early postoperative period. According to the Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) results obtained in the early postoperative period, the patients were divided into 2 groups as Group 1 for those with negative PCR and Group 2 for those with positive PCR. After that a total of 59 patients who were found to have COVID-19 were divided into 2 groups as survivors and non-survivors. Results: There were 118 (66.6%) patients in Group 1 and 59 (33.3%) in Group 2. The mean ages of patients in Group 1 and Group 2 were 64.5 ± 9.8 years and 61.9 ± 10.1 years, respectively (p = 0.174). Mortality was significantly higher in Group 2 (n = 24, 40.6%) compared Group 1 (n = 2, 1.6%) (p < 0.001). After that a total of 59 patients who were found to have COVID-19 were divided into 2 groups as survivors (n = 35, 59.3%) and non-survivors (n = 24, 40.7%). There was no statistically significant difference between the groups in terms of gender, smoking, diabetes mellitus, hypertension, chronic renal failure, chronic obstructive pulmonary diseas rates and surgery types (p > 0.05). Conclusions: The COVID-19 pandemic has significantly affected our cardiovascular surgery practice. In addition to being negative for PCR at least 2 times in routine preoperative preparations, obtaining endobronchial lavage samples for PCR testing from the endotracheal tube in the early postoperative period plays an important role in patient management.